ANALISIS PERENCANAAN DAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA PADA KANTOR BADAN PENGELOLA KEUANGAN DAERAH (BPKD) PROV. SUL-SEL TAHUN 2016-2017 - Lilly Ibrahim; Muh Nur Abdi; Elyang Elyang (Universitas Muhammadiyah Makassar, 2020)
This study aims to determine whether the practice of Islamic Corvorate Social Responsibility affects the This study aims to determine the budget planning with the effectiveness and efficiency of the realization of the revenue and expenditure budget in the Badan Pengelola Keungan Daerah (BPKD) of South Sulawesi Province 2016 to 2017. The type of research used is descriptive research with a quantitative approach. The data processed is a summary of the Budget Work Plan and Budget Realization at the Badan Pengelola Keungan Daerah (BPKD) from 2016 to 2017 obtained from the annual report of the regional financial management body. The calculation technique used in the study is calculating the effectiveness ratio and efficiency ratio of Badan Pengelola Keungan Daerah budget realization. While the data analysis technique used in the study was to calculate the effectiveness and efficiency of the realization of the Badan Pengelola Keungan Daerah budget through the results of the overall income and expenditure budget. Based on the results of calculations and data collection on budget planning Badan Pengelola Keungan Daerah managed to prepare and plan its budget well until the realization stage, but the realization of the budget has been running quite effectively but less efficiently in 2016 to 2017, which is due to spending greater than income.